Metabolism of oxyfluorfen by actinobacteria Micrococcus sp. F3Y - Yao, Li; Wen, Yue; Sha, Yuting; Wang, Leqin; Bi, Xianrui; Si, Shuhan; Shen, Min; Zhang, Shusong; Ni, Haiyan (Frontiers in Microbiology, 2025)
Oxyfluorfen, a potent diphenyl ether herbicide, has raised significant environmental concerns due to its persistence, toxicity to non‒target organisms, and potential carcinogenicity. Microbial degradation plays a crucial role in mitigating its impact, yet complete mineralization pathways remain poorly understood. In this study, we isolated Micrococcus sp. F3Y, an oxyfluorfen‒degrading actinobacterium, and evaluated its degradation efficiency in yeast powder‒supplemented mineral medium (YPM) medium and oxyfluorfen‒contaminated soil. Optimal conditions, pH, temperature, initial optical density (OD600nm) were determined. Metabolites were analyzed via UPLC/Q‒TOF MS, and a putative gene cluster was identified through draft genome sequencing. Strain F3Y completely degraded 100 mg/L oxyfluorfen within 12 h under optimal conditions (pH 7.0, 30°C, OD600=2.0), maintaining over 55% efficiency at 25‒42°C and above 62% across a pH range of 6.5‒8.0. When the initial oxyfluorfen concentration was ≤150 mg/L, the degradation rate exceeded 74%. Moreover, in oxyfluorfen‒contaminated soil (0.06 mg/kg), inoculation with strain F3Y restored soybean (Glycine max) growth, increasing shoot length from 4.22 cm (severely inhibited) to 28.8 cm, a nearly 7‒fold improvement. Additionally, F3Y achieved 98.2% degradation of oxyfluorfen (50 mg/kg) within 25 d in unsterilized soil. Eleven metabolites, including six new intermediates, were identified. Based on these, two novel degradation pathways were proposed: one initiated by nitro reduction and the other by diaryl ether cleavage. Both pathways culminated in aromatic ring opening and complete mineralization. In addition, a potential 24.3 kb gene cluster, pao, was suggested. Comprising thirteen genes, it was hypothesized to participate in the ring cleavage of intermediate products during oxyfluorfen degradation. This study provided the first comprehensive evidence of Micrococcus mediated oxyfluorfen mineralization, offering new insights into actinobacterial metabolic versatility. With its high degradation efficiency, environmental resilience, and detoxification ability, F3Y was an ideal candidate for bioremediation. These finding not only enhanced the understanding of herbicide degradation but also provided a sustainable solution to address oxyfluorfen contamination in agricultural and natural ecosystems.